Occupational Exposure to Low Concentrations of Lead Dust and Oxidative Stress in Mine Workers - Fateme Kooshki; Masoud Neghab; Fatemeh Rahimian; Fereshteh Aliasghari; Esmaeel Soleimani (Journal of Health Sciences and Surveillance System)
Background: Several epidemiological studies have reported associations between high levels of lead exposure and oxidative stress (OS). However, research on the effects of low-level lead exposure remains limited. This study aims to assess the relationship between OS parameters and exposure to low concentrations of lead dust in mine workers.Methods: This cross-sectional study evaluated 73 lead-exposed workers and 70 age- and sex-matched non-exposed individuals. Demographic data and occupational and medical history were collected through questionnaires. Workers’ exposure to lead dust was assessed by air monitoring, and blood lead levels (BLLs) were calculated based on inhalation exposure. Blood samples were collected to determine OS parameters. Data were analyzed using SPSS version 21.0.Results: The mean exposure of workers to lead dust was 24 μg/ m³ (range: 1.5 to 185 μg/m³), which complied with the OSHAPEL and ACGIH TLV-TWA standards for lead dust. The BLL in the exposed workers was found to be 45.47 μg/dL. A significant association was observed between the SOD/MDA ratio and exposure to lead dust. Additionally, a borderline negative association between lead exposure and superoxide dismutase (SOD) activity was found. A significant relationship was noted between workers’ BMI and OS biomarkers.Conclusion: This study’s findings suggest that chronic exposure to lead dust may affect OS biomarkers, even at concentrations below the current OSHA-PEL and ACGIH TLV-TWA.